Facilitating Discussion of Theory and Practice in Education Seminars - Bailey Herrmann; Jessica R Gallo (Networks: An Online Journal for Teacher Research, 2018)
Field experience seminars, discussion-based courses paired with school-based practicum experiences, provide a space for teacher candidates to discuss the theories they study in their university classes and the practices they observe and implement in their school placements. This article describes an action research study that examines teaching techniques that promote discussion in English education seminar courses. The purpose of this research was to collaboratively develop teaching approaches that would help teacher candidates bridge ideas about theory and practice in their development as aspiring teachers. The conversations that challenged the teacher candidates to think critically and theoretically about their classrooms were transformative moments in our seminar classes.
Keywords: teacher education; field experience seminars; reflective discussion